Convergence of VAT Rates Between 1995 and 2010 - Květa Kubátová; Pavla Holešovská (European Financial and Accounting Journal, 2014)
Consumption taxes have been harmonized in the EU countries since 1993 and a great attention is paid to their convergence in the EU. The EU directives harmonize tax administration, tax bases and set minimal applicable rates. The aim of the article is to find out if VAT systems of the EU countries really converged during the period 1995 and 2010, in consequence of harmonization. The subject of investigation is standard and reduced VAT rates, VAT revenues as a share in GDP and implicit rates of consumption taxes. Investigative methods are analysis of these indexes development, t-tests and F-tests. There were used data from Eurostat and the European Commission for the statistics. Except for standard VAT rates, there was no decrease of indexes variability and therefore tax systems did not converge.
Keywords: H20; 650; VAT harmonization; Value added tax; The European Union; F-test; Convergence of VAT rates